Mechanical damages in solid electrolyte battery due to electrode volume changes. (1st August 2022) - Budiman, Bentang Arief; Saputro, Andy; Rahardian, Samuel; Aziz, Muhammad; Sambegoro, Poetro; Nurprasetio, Ignatius Pulung
Abstract: Mechanical damages in solid electrolytes of solid-state battery (SSB) during the charging-discharging process remain a challenging issue for battery implementation. This paper demonstrates a numerical simulation of the damages in Li10 GeP2 S12 (LGPS) solid electrolyte of SSB due to compressive loading generated by electrode volume changes. Three models of anode/electrolyte/cathode arrangements were examined numerically with different expansion-shrinkage behavior. Crack formation inside the electrolyte models was realized by inserting cohesive elements, following traction-separation law. The result shows that when the cathode shrunk and the anode expanded, as occurs in NCM/LGPS/In configuration, the mechanical damages inside the LGPS solid electrolyte are more severe. Due to high-stress generation, there is a plastic deformation in the electrolyte and debonding at the electrode-electrolyte interface. The cracks also appear in both center and edge of the electrolyte because of high-stress concentration. These cracks do not occur when Li4 Ti5 O12 (LTO) anode with a very low expansion rate is used. This finding confirms that SSB was prone to mechanical damages due to expansion-shrinkage behavior in the electrodes, meaning that the mechanical strength of SSB material constituents must be considered in designing long-lasting SSB. Highlights: Simulation for investigating solid-state battery's mechanical damages due to electrodes volume changes has been conducted. Plastic deformation, interfacial debonding, and crack propagation were simultaneously simulated in the developed model. Indium has a problem as an anode due to the high expansion rate during battery charging and discharging. Anode expansion and cathode shrinkage are the worst configuration since they significantly damage solid electrolytes.